Interfacial Structure of PtNi Surface Alloy on Pt(111) Electrode for Oxygen Reduction Reaction - Kumeda, Tomoaki (ACS Omega, 2017)
[Image: see text] The interfacial structure and activity for the oxygen reduction reaction (ORR) were investigated on a PtNi surface alloy on a Pt(111) electrode (PtNi/Pt(111)). The PtNi surface alloy was prepared by thermal annealing of Ni(2+) modified on Pt(111) at 573–803 K. After optimizing the alloying temperature and the amount of added Ni, the ORR current density of PtNi/Pt(111) at 0.9 V (reversible hydrogen electrode) is enhanced 9.5 times compared with that of Pt(111), and the activity is decreased by 24% after 1000 potential cycles. The atomic composition and subsurface structure of PtNi/Pt(111) were determined by in situ infrared reflection–absorption spectroscopy and X-ray diffraction. The surface contains a (111)-oriented Pt-skin and the subsurface of the 2nd–5th layers of the PtNi alloy contains less than 11% Ni atoms. The layer spacings of the surface alloy layers are slightly expanded compared with those of bare Pt(111). Homogeneous alloying with a small amount of Ni in the subsurface layers achieves the high ORR activity and durability.